Evaluation of the nursing notations based on nursing process - Ochoa-Vigo, Kattia; Pace, Ana Emilia; Rossi, Lídia Aparecida; Hayashida, Miyeko (Revista da Escola de Enfermagem da USP, 2001)
This is a retrospective study that analyzed the nursing notations in a Specialized Unit which develops the care to the patient based on Nursing Process. The data were collected through two promptuaries utilizing instrument constructed for this purpose. Aspects which valuate appearance and content were considered in the analysis. The nursing assistant was distinguished in the results considering the bigger number of extensive and not very specific notations, and in the registrations achieved by the nurse, it was observed a bigger number of legible and objective notations. By expressing the Nursing work, greater investments must be made to become more objective and full the nursing notations.